MODERN INTERACTION IN FOREIGN LANGUAGE TEACHING - Jumanazarova Xurliman Maratovna (TADQIQOTLAR, 2025)
Annotation: English teaching is not so an easy job for the educators. It requires concrete syllabus including teaching methods, set of games and visual aids. The article explains the types of approaches and methods; aims of teaching EFL, focusing lessons to four skills: reading, writing, listening and speaking.